In vitro Measurement of Membrane Attack Complex in RPE Cells - Kelly Mulfaul; Sarah Doyle (Bio-Protocol, 2021)
Initiation of the complement system results in the formation of a multiprotein pore termed the membrane attack complex (MAC, C5b-C9). MAC pores accumulate on a cell surface and can result in cell lysis. The retinal pigment epithelium (RPE) is a single monolayer of pigmented epithelial cells located at the posterior poll of the eye that forms the outer blood retinal barrier. RPE cells are highly polarized with apical microvilli and basolateral contact with Bruch’s membrane. In order to obtain biologically relevant polarized RPE cultures in vitro, RPE cells are seeded onto the apical side of a transwell filter and cultured for 4 weeks in low serum media. MAC formation on RPE cells has been reported to be sub-lytic. MAC formation can be achieved in vitro by introduction of normal human serum (NHS) to media following serum starvation for 24 h. NHS contains all serum complement proteins required to initiate complement activation and MAC formation. We combined in vitro RPE polarization and complement activation to visualize MAC formation in vitro utilizing confocal microscopy allowing for high resolution MAC imaging.